Answer:
A. 8.3
B.18.7
C. 10.4
D. 1.04
Explanation:
p(x) = 0.03x² + 0.56x + 6.35
A. Determination of p(3)
p(x) = 0.03x² + 0.56x + 6.35
x = 3
p(3) = 0.03(3)² + 0.56(3) + 6.35
p(3) = 0.03(9) + 1.68 + 6.35
p(3) = 0.27 + 1.68 + 6.35
p(3) = 8.3
B. Determination of p(13)
p(x) = 0.03x² + 0.56x + 6.35
x = 13
p(13) = 0.03(13)² + 0.56(13) + 6.35
p(13) = 0.03(169) + 7.28 + 6.35
p(13) = 5.07 + 7.28 + 6.35
p(13) = 18.7
C. Determination of p(13) – p(3)
From A and B above,
p(13) = 18.7
p(3) = 8.3
p(13) – p(3) = 18.7 – 8.3
p(13) – p(3) = 10.4
D. Determination of p(13) – p(3) / 13 – 3
From C above,
p(13) – p(3) = 10.4
p(13) – p(3) / 13 – 3 = 10.4/ 13 – 3
= 10.4 / 10
= 1.04